Experiences and Perceptions of Chinese Elderly Dry Eye Patients Seeking Health Behavior Management: A Qualitative Study Based on a Health Belief Model - Tang Y; Yi L; Ma Y; Liu Q; Zhang Y; Wang S; Zeng J; Cheng W; Li R (Journal of Multidisciplinary Healthcare)
Yuanyuan Tang,1 Lan Yi,2 Yanjie Ma,1 Qiqi Liu,3 Yifan Zhang,3 Simeng Wang,1 Jia Zeng,1 Wenlin Cheng,4 Rui Li4 1Wuxi Medical College, The Jiangnan University, Wuxi, Jiangsu Province, 214122, People’s Republic of China; 2Ophthalmology Centre, The Tongren Hospital Shanghai Jiao Tong University School of Medicine, Shanghai, 200335, People’s Republic of China; 3Nursing College, The Beihua University, Jilin, Jilin Province, 132000, People’s Republic of China; 4Department of Nursing, The Tongren Hospital Shanghai Jiao Tong University School of Medicine, Shanghai, 200335, People’s Republic of ChinaCorrespondence: Rui Li, Department of Nursing, The Tongren Hospital Shanghai Jiao Tong University School of Medicine, No. 1111 Xianxia Road, Changning District, Shanghai, People’s Republic of China, Tel +8618616365160, Email 18616365160@163.comAim: This study aims to explore the life experiences and health behavior management experiences of elderly patients with dry eye disease, and to provide a reference for improving the health status of patients with dry eye disease.Methods: A qualitative phenomenological design was employed to collect data from 16 dry eye patients who visited the eye clinic of a tertiary hospital in Shanghai, China, from October to December 2024, by conducting face-to-face semi-structured interviews, and analyzing the data using the Colaizzi 7-step analysis method. Interviews were transcribed verbatim, and themes were coded and extracted using NVivo 14.0.Results: The participants, aged between 60 and 78 years, mostly had mild to moderate levels of dry eye. Based on the theoretical model of the Health Belief Model, five main themes and eleven sub-themes were summarized from the analysis: (a) Perceived threat of disease (Perceived severity, Perceived susceptibility); (b) Perceived benefits (Perceived sense of gain, Improved quality of life); (c) Perceived barriers (Lack of willingness to manage behavior, Insufficient intrinsic motivation, Cognitive misconceptions); (d) Low self-efficacy (Lack of confidence in responding, Negative coping style); (e) Perception of behavioral cues (Lack of external support, Perception of self-management).Conclusion: This study found an interaction between reduced threat perception and inadequate health behavior management in elderly dry eye patients, and future research is needed to develop more specific and feasible intervention programs to encourage patients to move from passive treatment to active management.Keywords: elderly, dry eye disease, health behavior, qualitative research, relevance to clinical practice